2019
DOI: 10.1016/s2095-3119(17)61845-8
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity and sublethal effects of some frequently-used biopesticides on the predator Cyrtorhinus lividipennis Reuter (Hemiptera: Miridae)

Abstract: The green miridbug, Cyrtorhinus lividipennis, is an important predator of the rice brown planthopper, Nilaparvata lugens. In this study, the selective toxicity of seven commercial biopesticides for C. lividipennis was examined under laboratory conditions; abamectin was the most selective to C. lividipennis, followed by matrine and azadirachtin. Veratridine, rotenone, Bacillus thuringiensis and Beauveria bassiana showed less selectivity for C. lividipennis. Subsequently, matrine, abamectin and azadirachtin were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Matrine even had some positive effects on H. variegata , with contact exposure being associated with higher rates of adult eclosion in the offspring generation, while oral (stomach) toxicity shortened pupal developmental time in the offspring generation. Our results were similar to existing studies, for example, Dai et al (2019) demonstrated that matrine is selective to the predatory mirid C. lividipennis and had no effect on its predation of Nilaparvata lugens . Tian et al (2020) found that matrine had no obvious influence on the densities of coccinellids, spiders, or parasitoids in tea plantations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Matrine even had some positive effects on H. variegata , with contact exposure being associated with higher rates of adult eclosion in the offspring generation, while oral (stomach) toxicity shortened pupal developmental time in the offspring generation. Our results were similar to existing studies, for example, Dai et al (2019) demonstrated that matrine is selective to the predatory mirid C. lividipennis and had no effect on its predation of Nilaparvata lugens . Tian et al (2020) found that matrine had no obvious influence on the densities of coccinellids, spiders, or parasitoids in tea plantations.…”
Section: Discussionsupporting
confidence: 93%
“…It controls many kinds of pests, including lepidopteran larvae, e.g., Plutella xylostella L. (Lepidoptera: Plutellidae), Spodoptera litura Fabricius (Lepidoptera: Noctuidae), Helicoverpa armigera Hübner (Lepidoptera: Noctuidae), aphids e.g., Myzus persicae Sulzer (Hemiptera: Aphididae), Brevicoryne brassicae L. (Hemiptera: Aphididae), Aphis craccivora Koch (Hemiptera: Aphididae), Sitobion avenae Fabricius (Hemiptera: Aphididae), A. citricola van de Goot (Hemiptera: Aphididae), Macrosiphum rosirvorum Zhang (Hemiptera: Aphididae), spider mites e.g., Panonychus citri McGregor (Acariformes: Tetranychidae), psyllids e.g., Diaphorina citri Kuwayama (Hemiptera: Chermidae), plant bugs e.g., Apolygus lucorum Meyer-Dür (Hemiptera: Chermidae), and whiteflies e.g., Aleurocanthus spiniferus Quaintance (Hemiptera: Aleyrodidae) (Fang et al 2018, Ma et al 2018, Shah et al 2020, Tian et al 2020). Its safety, conversely, has been demonstrated to several groups of natural enemies, including both predators e.g., ladybugs, spiders, and the mirid Cyrtorhinus lividipennis Reuter (Hemiptera: Miridae) and parasitoids e.g., Aphidius matricariae Haliday (Hymenoptera:Aphytis) (Ali et al 2017, Fang et al 2018, Dai et al 2019, Jack et al 2022). In general, matrine has significant potential for use in pest control.…”
Section: Introductionmentioning
confidence: 99%
“…Azadirachtin is registered in the United States as a general-use pesticide with a toxicological class Environmental Protection Agency (EPA) of IV (relatively non-toxic). Azadirachtin seems to be selective, non-mutagenic, and readily degradable and has also been reported as safer for non-target organisms and beneficial organisms (Medina et al, 2004;Cordeiro et al, 2010;Mordue et al, 2010;Celestino et al, 2014;Dai et al, 2019); however, the presumed safety of azadirachtin has been questioned, especially, in relation to natural enemies and pollinators (Barbosa et al, 2015;Lima et al, 2015;Xavier et al, 2015;Bernardes et al, 2017Bernardes et al, , 2018Francesena and Schneider, 2018). Nevertheless, semifield and field studies may enable to reliably predict potential side effects of azadirachtin on non-target insects.…”
Section: Azadirachtin: Properties and Insecticidal Activitiesmentioning
confidence: 99%
“…Azadirachtin is registered in the United States as a general-use pesticide with a toxicological class Environmental Protection Agency (EPA) of IV (relatively non-toxic). Azadirachtin seems to be selective, non-mutagenic, and readily degradable and has also been reported as safer for non-target organisms and beneficial organisms (Medina et al, 2004;Cordeiro et al, 2010;Mordue et al, 2010;Celestino et al, 2014;Dai et al, 2019); however, the presumed safety of azadirachtin has been questioned, especially, in relation to natural enemies and pollinators (Barbosa et al, 2015;Lima et al, 2015;Xavier et al, 2015;Bernardes et al, 2017Bernardes et al, , 2018.…”
Section: Insecticidal Properties Of Azadirachtinmentioning
confidence: 99%